Liquefied Natural Gas (LNG) Safe Loading and Unloading Model in Port Operation - Kader, Ab Saman Abd; Oladokun, Sulaiman; Shamsuri, W.N.W. (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2015)
This project presents the study of the safe procedures of LNG loading and unloading operation in port. The purpose of this study is to maintain the safety record of LNG operation for this roughly forty years. The study is carried out by performing ‘one to one interview’ with the port’s safety officer. Then, the collected data from the personal interview is analyzed using Hazard Identification (HAZID) approach. The detail procedures, technical data, and explanation from port’s safety as an expertise in LNG handling field could be needed to determine the potential improvement that could trigger the idea to develop a generic safety model which is refined and improved of the existent holistic model that being reviewed in this study. The model developed in this study is to be applied onto either loading or unloading LNG terminal all over the world. This model is expected to meet the aim of minimizing the unsafe act and near miss which is always be the initiation point of harmful incident and accident. Model which has been developed is an improved and refined version of a generic safety model. The model developed describes the integration of technologies within the system of working competency which also reconsidering the individual performance. In the same time, it aimed to reduce the probabilities of the crews or operators to engage with unsafe act which always introduce the consequence of near miss, which is to be minimized in this research. The model developed in this study is called ‘H-T-D’ safety model, which stand for human factor, technical handling, and design element.